2018
DOI: 10.1002/hep.29885
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 promotes liver fibrosis by preventing miR‐19b‐3p‐mediated inhibition of CCR2

Abstract: Chronic liver disease mediated by activation of hepatic stellate cells (HSCs) and Kupffer cells (KCs) leads to liver fibrosis. Here, we aimed to investigate the molecular mechanism and define the cell type involved in mediating the sphingosine kinase (SphK)1‐dependent effect on liver fibrosis. The levels of expression and activity of SphK1 were significantly increased in fibrotic livers compared with the normal livers in human. SphK1 was coexpressed with a range of HSC/KC markers including desmin, α‐smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 41 publications
1
99
0
Order By: Relevance
“…Sphingosine kinases (two isoforms, SPHK1 and SPHK2) catalyze the formation of sphingosine 1‐phosphate (S1P), a lipid mediator that functions in mammalian cells as an intracellular second messenger, as well as a ligand for S1P‐specific G‐protein‐coupled receptors . SPHK1 can be expressed in many types of cells, including monocytes, macrophages, hepatic stellate cells, and smooth muscle cells . Previous studies have shown that SPHK1 is mainly expressed in M2b and suggested that it can be used as a marker for M2b monocytes/macrophages .…”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
See 2 more Smart Citations
“…Sphingosine kinases (two isoforms, SPHK1 and SPHK2) catalyze the formation of sphingosine 1‐phosphate (S1P), a lipid mediator that functions in mammalian cells as an intracellular second messenger, as well as a ligand for S1P‐specific G‐protein‐coupled receptors . SPHK1 can be expressed in many types of cells, including monocytes, macrophages, hepatic stellate cells, and smooth muscle cells . Previous studies have shown that SPHK1 is mainly expressed in M2b and suggested that it can be used as a marker for M2b monocytes/macrophages .…”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
“…64 SPHK1 can be expressed in many types of cells, including monocytes, macrophages, hepatic stellate cells, and smooth muscle cells. 34,[65][66][67][68] Previous studies have shown that SPHK1 is mainly expressed in M2b and suggested that it can be used as a marker for M2b monocytes/macrophages. 1,34,47,48 However, Mantovani and his colleagues reported that SPHK1 is expressed at higher levels in M1 than M2 cells.…”
Section: Sphk1mentioning
confidence: 99%
See 1 more Smart Citation
“…Liver fibrosis is a wound‐healing response to chronic liver injury . During chronic injury, the liver parenchyma is gradually replaced with excessive extracellular matrix, eventually causing disruption of liver architecture and the loss of liver function.…”
Section: Introductionmentioning
confidence: 99%
“…The above data have extruded the role of iRhom2 in HFD-induced adipose inflammation and macrophages activation. In view of such situation, we attempted to deeply explore the role for iRhom2 in macrophages in adipose inflammation using bone marrow transplantation (BMT), a method that has been widely used for changing gene expression of macrophages (26,27). The lethally irradiated WT mice were transplanted with bone marrow cells isolated from iRhom2 KO mice and/or WT mice to generate a KOBM→WT mice.…”
Section: Myeloid Cell-specific Irhom2 Knockout Reduces High Fat Diet-mentioning
confidence: 99%